2018
DOI: 10.1016/j.ebiom.2018.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol ameliorates cisplatin nephrotoxicity by inhibiting NF-κB and improving mitochondrial function

Abstract: BackgroundCelastrol is an active ingredient of Chinese medicine Tripterygium wilfordii which is clinically used to treat the immune diseases. Currently, celastrol is documented as a potent agent for treating cancer and inflammatory disorders. This study was to investigate the effect of celastrol on cisplatin nephrotoxicity and the underlying mechanism.MethodsMale C57BL/6 mice were treated with cisplatin (20 mg/kg) with or without celastrol treatment (1 and 2 mg/kg/day). In vitro, human proximal tubule epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(105 citation statements)
references
References 41 publications
7
98
0
Order By: Relevance
“…NF‐κB activation in the cisplatin‐administered rat's kidneys is a direct consequence of the increased generation of ROS. Numerous studies have established an inflammatory response being next to cisplatin administration in experimental animals . Few research studies have reported the role of elevated expression of NF‐κB in nephrotoxicity in humans and experimental animals .…”
Section: Discussionmentioning
confidence: 99%
“…NF‐κB activation in the cisplatin‐administered rat's kidneys is a direct consequence of the increased generation of ROS. Numerous studies have established an inflammatory response being next to cisplatin administration in experimental animals . Few research studies have reported the role of elevated expression of NF‐κB in nephrotoxicity in humans and experimental animals .…”
Section: Discussionmentioning
confidence: 99%
“…Celastrol possesses multiple pharmacological effects and showed potent anti-inflammatory effect against many disease models, [10][11][12][13] and however, few reports can be seen regarding the anti-inflammatory potential of celastrol in liver fibrosis. SIR2 is a family of histone deacetylases and is widely distributed in cells with multiple functions.…”
Section: The Active Ingredients Extracted From Traditional Chinesementioning
confidence: 99%
“…Panaxynol treatment reduced the serum creatinine and BUN in mice with cisplatin-induced kidney injury. Several reports have indicated that various inflammatory factors such as TNF-α, IL-6, MCP-1, and COX-2 are upregulated in cisplatin-induced nephrotoxicity in both humans and rodents [40,41]. The panaxynol-treated group exhibited significantly decreased COX-2 mRNA expression and slightly decreased MCP-1 mRNA expression in the kidneys compared to the cisplatin alone group.…”
Section: Discussionmentioning
confidence: 94%